2018
DOI: 10.1038/s41561-018-0061-4
|View full text |Cite|
|
Sign up to set email alerts
|

Corrugated megathrust revealed offshore from Costa Rica

Abstract: Exhumed faults are rough, often exhibiting topographic corrugations oriented in the direction of slip; such features are fundamental to mechanical processes that drive earthquakes and fault evolution. However, our understanding of corrugation genesis remains limited due to a lack of in situ observations at depth, especially at subducting plate boundaries. Here we present 3D seismic reflection data of the Costa Rica subduction zone that image a shallow megathrust fault characterized by (1) corrugated and (2) ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…The correlation between unconformities of both segments of the margin is unfeasible since they are eroded at Domain II, where uplift is maximal. The three unconformities of Domain I agree with those interpreted by Edwards, Kluesner, Silver, Brodsky, et al () across the 3‐D seismic cube and reflect the three recent tectonic phases undergone by the region, which were described by Vannucchi et al () based on the paleodepth record of the Pleistocene sediments recovered during IODP Expedition 334 at Sites U1379 and U1378 (Figures and ). These authors relate the uplift of the forearc basin from deep water to nearshore conditions (~800 m) at early Pleistocene (~2.3 Ma) with the arrival of the Cocos Ridge at the trench, while they connect the onset of the Cocos Ridge subduction later in the early Pleistocene (from 2.2 to 1.9 Ma) with high erosional rates at the base of the overriding plate that triggered net subsidence of ~1,200 m. Finally, they interpret the second pulse of uplift (~1,000 m) from the middle‐late Pleistocene to Holocene (from 1.9 Ma to present day) that interrupted subsidence, as the direct effect of the subduction of the thickened Cocos Ridge crust.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The correlation between unconformities of both segments of the margin is unfeasible since they are eroded at Domain II, where uplift is maximal. The three unconformities of Domain I agree with those interpreted by Edwards, Kluesner, Silver, Brodsky, et al () across the 3‐D seismic cube and reflect the three recent tectonic phases undergone by the region, which were described by Vannucchi et al () based on the paleodepth record of the Pleistocene sediments recovered during IODP Expedition 334 at Sites U1379 and U1378 (Figures and ). These authors relate the uplift of the forearc basin from deep water to nearshore conditions (~800 m) at early Pleistocene (~2.3 Ma) with the arrival of the Cocos Ridge at the trench, while they connect the onset of the Cocos Ridge subduction later in the early Pleistocene (from 2.2 to 1.9 Ma) with high erosional rates at the base of the overriding plate that triggered net subsidence of ~1,200 m. Finally, they interpret the second pulse of uplift (~1,000 m) from the middle‐late Pleistocene to Holocene (from 1.9 Ma to present day) that interrupted subsidence, as the direct effect of the subduction of the thickened Cocos Ridge crust.…”
Section: Discussionsupporting
confidence: 84%
“…Initially, Costa Rica was proposed to contain a large accretionary prism made of scraped and underplated sediment (e.g., McIntosh et al, ; Stoffa et al, ), but later, sampling with ODP drilling offshore Nicoya (Kimura et al, ) and extensive geophysical data support that the MAT is dominated by tectonic erosion (Ranero et al, ; Ranero & von Huene, ; von Huene et al, ). The MAT is characterized by long‐term subsidence (Ranero et al, ; Vannucchi et al, , ), supporting large‐scale tectonic erosion, although recent 3‐D seismic data offshore Osa Peninsula (see location in Figure S1) have shown that the structure may be laterally complex and may locally be characterized by short episodes of accretion and deformation associated to large subducting relief (Bangs et al, ; Edwards et al, ).…”
Section: Geological Settingmentioning
confidence: 92%
“…The corrugations correspond to ~ 10 ms lineations in a filtered map of S (Figure 4b), persist after depth conversion ( Figure 4c) and match high-amplitude lineations on the amplitude map of S ( Figure 4d). Corrugations observed on major slip surfaces, such as on oceanic detachment faults (Cann et al, 1997), are believed to form at depth and to parallel the displacement direction (Resor and Meer, 2009;Edwards et al, 2018), but have never previously been observed on a major extensional detachment buried beneath fault blocks at a rifted margin before the acquisition of the Galicia 3D volume. In both time and depth, the corrugations exhibit an oceanward change in orientation from E-W to ESE-WNW; the identification and changing orientation of the corrugations on S demonstrate that the overlying extended continental crust slipped on S and that the direction of extension changed oceanwards, remaining parallel to the corrugations (Figure 4), during the rifting.…”
Section: The 3d Geometry Of the S Detachmentmentioning
confidence: 98%
“…In this study, we focus on the effect of fault roughness on the nucleation processes. Although most previous studies model a fault surface as a single plane, many filed observations report that natural faults have “roughness” and its spatial scale ranges from micron scales to map scales (e.g., Brown & Scholz, ; Candela et al, ; Edwards et al, ; Power et al, ; Power & Tullis, ; Renard & Candela, ; Sagy et al, ). The roughness is characterized as self‐affine fractal.…”
Section: Introductionmentioning
confidence: 99%